Clinical research on ocular myasthenia gravis and related neuromuscular disorders: A systematic review and overview - MengYu Wang; ZhaoYuan Sheng (Clinical and Investigative Medicine, 2026)
Abstract Background: Ocular myasthenia gravis is an acquired autoimmune disorder primarily manifesting clinically as ptosis, diplopia, ocular muscle paralysis, and restricted ocular motility. However, its clinical presentation overlaps with multiple ocular pathologies, leading to frequent misdiagnosis in clinical practice and adversely affecting patient prognosis. Hence, we conducted a systematic review and analysis of relevant literature. Methods: From 1 January 2020 to 31 August 2025, three databases (PubMed, Web of Science and China National Knowledge Infrastructure) were searched. This study focused on ocular myasthenia gravis, incorporating neuromuscular disorders presenting with ocular abnormalities. Keywords were selected based on disease guidelines and common clinical scenarios (frequent differential diagnoses or misdiagnoses), and the keywords ocular myasthenia gravis , myasthenia gravis , motor nerve paralysis , ptosis , diabetic eye muscle paralysis , and thyroid-associated ophthalmopathy were ultimately selected. Eight studies published prior to 2020 were identified. Despite their age, these studies were included in the present review due to their relevance to the study's scope and their value for scholarly discussion. Results: Ocular myasthenia gravis is caused by autoantibody-mediated damage to the neuromuscular junction and impaired signal transmission, typically presenting with ptosis, diplopia, and restricted eye movements. Due to the lack of a diagnostic gold standard, ocular myasthenia gravis is easily confused with oculomotor nerve palsy, ptosis, diabetic ophthalmoplegia, and thyroid-associated ophthalmopathy, leading to misdiagnosis or missed diagnosis. This may delay treatment or allow progression to generalized myasthenia gravis. Additionally, personalized treatment is required for specific populations with myasthenia gravis. Adolescents with ocular myasthenia gravis require greater caution in medication use, where traditional Chinese medicine offers a potential alternative for children with drug restrictions. Pregnant patients with myasthenia gravis require assessment of delivery methods and anesthesia risks. Conclusion: The diagnosis of ocular myasthenia gravis remains challenging, requiring differentiation from multiple similar conditions to avoid misdiagnosis and disease progression. Additionally, individualized treatment for patients with myasthenia gravis in special populations, such as children and pregnant women, is crucial. For ocular myasthenia gravis, optimizing diagnostic criteria, achieving early differential diagnosis, and exploring safer and more effective therapeutic agents are urgent issues that need to be addressed.